Reconstruction of Digital Twin for Traffic Accident Investigation Using Drone Photogrammetry - Polsai, Wasu; Waisurasingha, Chattichai; Klungboonkrong, Pongrid; Waisurasingha, Chutima (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
The purpose of this study was to apply UAV imaging surveys to record the damage inflicted to light-vehicles following an accident in the form of a 3D model, and to compare the completeness of the three-dimensional model obtained by visual survey analysis of unmanned aerial vehicles processed by semi-automatic and automated methods based on the experts in field of photogrammetric surveying. This is because the photogrammetric surveying could be used to fully reconstruct the accident scene in terms of the vehicle details . In addition, the recorded events in the dimension of accident reconstruction could be used to realize the accident details. Therefore, this is an important innovation that could help to ensure the archiving of digital evidence. The study examined comparative integrity through open-source, low-cost, professional, and cloud-processing software. The results reflected how well each software performed. The positional accuracy obtained by professional software processing was at an acceptable level.